Biosynthesis of Polyamide 4, a Biobased and Biodegradable Polymer - IWAN SASKIAWAN (Indonesian Society for microbiology, 2008)
Polyamide 4, which is composed of repeating unit of g-aminobutyric acid (GABA), is a biobased and biodegradable polymer since it can be synthesized from renewable material instead of fossil-based material. GABA is produced by decarboxylation of glutamate (Glu) using glutamate decarboxylase (GAD: EC 4.1.1.15), which is produced by some microorganisms. In this study, enzymatic conversion of GABA from glutamate by Lactococcus lactis and Escherichia coli cell and chemical polymerization of GABA to polyamide 4 were revealed. The results show that GAD activity of E. coli was higher than that of L. lactis. The treatment of E. coli cell by heating and sonication increased the GAD activity and conversion rate of glutamate to GABA was up to 70.5%. The optimum temperature for this conversion is 37ºC. On the other hand, chemical synthesis of polyamide 4 was catalyzed by heating GABA at 215ºC for 2 minutes